Implementasi Customer Relationship Management (CRM) Berbasis Website Pada Satu Potret Fotografi - Scholastica Larissa Zefira Lewoema; Raditha Larasaty; Putri Taqwa Prasetyaningrum (Journal of Information System and Artificial Intelligence, 2024)
Satu Potret Photography is a photography service company that provides various photo services, such as family photos, product photos, graduation photos, and other services. To improve the quality of service and customer loyalty, the company wants to implement an information system based on CRM (Customer Relationship Management). The purpose of this research is to design and implement a CRM information system using Wordpress as a popular and easy-to-use website creation platform. This CRM information system has features such as photography service reservation, customer testimonials, and catalog packages. This CRM information system is expected to support the company in offering promotions that match the customer’s wishes. That way, the company can improve service, sales, and build a good relationship between the company and customers.